Kajian Latar Belakang Sejarah Dan Budaya: Makna Teks Dalam Konteks Hermeneutika Alkitab - Intan Anggreni; Bobby Kurnia Putrawan (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2022)
Beginning in the 4th century (319) because it teaches heresy in terms of the Trinity, this heresy was taught by Arius, a priest from Alexandria, he wanted to simplify the mystery of the Trinity, here is a summary of heresy arianism heresy: Christ the son of God was created with the free will of God the Father , Christ the Son is not equally eternal (beginning and without end) with the Father, but has a beginning, Christ the Son is not of the same essence as God the Father, God the Father is infinitely more glorious than Christ the Son, God is not a Trinity in a manner condrat . The meaning of the Holy Spirit in the Bible. The purpose of this paper is to describe the theological meaning of the Holy Spirit in the Bible. By analyzing the text according to the principles of exegesis, To get the meaning contained in the context of the meaning of the Holy Spirit in the Bible. The results of this analysis will provide knowledge about God so that every believer will receive the Holy Spirit and eternal life. The meaning of the Holy Spirit in the Bible, namely: first, the Holy Spirit accompanies His Word. The Bible explains that the Holy Spirit is the Spirit of truth who testifies about the Lord Jesus and accompanies His word, meaning that God's call is not a secret call, but the work of the Holy Spirit that encourages us to repent and accept Jesus as Lord. Second, the Role of the Holy Spirit. The Holy Spirit teaches the Truth and leads into all truth. Third, the work of the Holy Spirit. The same person played a role in inspiring and in revealing the secrets of the word. In other words, that the Holy Spirit actively supports the ministry of Jesus Christ in the work of salvation for sinful mankind. Diawal abad ke-4 (319) karena mengajarkan ajaran sesat dalam hal Trinitas, bidaah ini diajarkan oleh Arius, seorang imam dari Alexandria, ia ingin menyederhanakan misteri Trinitas, berikut adalah ringkasan ajaran sesat heresi arianism: Kristus putra Allah diciptakan dengan kehendak bebas Allah Bapa, Kristus Sang Putera tidak sama-sama kekal ( tak berawal dan tak berakhir) dengan Bapa, melainkan mempunyai sebuah awal, Kristus sang Putra tidak sehakekat dengan Allah Bapa, Allah Bapa secara tak terbatas lebih mulia dari pada Kristus Sang Putera, Tuhan bukan Trinitas secara kondratnya. Makna Roh Kudus dalam Alkitab. Tujuan penulisan ini untuk mendeskripsikan makna Roh Kudus dalam Alkitab secara teologis. Dengan analisis teks sesuai dengan prinsip-prinsip eksegesis, Untuk mendapatkan makna yang terkandung didalam konteks makna Roh Kudus dalam Alkiab. Hasil analisis ini akan memberi pengetahuan tentang Allah sehingga setiap orang yang percaya akan menerima Roh Kudus dan kehidupan kekal. Makna Roh Kudus dalam Alkitab yaitu: pertama, Roh Kudus Menyertai FirmanNya. Alkitab menjelaskan Roh Kudus adalah Roh kebenaran yang bersaksi tentang Tuhan Yesus dan menyertai firman-Nya artinya panggilan Tuhan bukanlah panggilan rahasia, melainkan kerja Roh Kudus yang mendorong kita kepada pertobatan dan menerima Yesus sebagai Tuhan. Kedua, Peran Roh Kudus. Roh Kudus mengajarkan Kebenaran dan memimpin kedalam seluruh kebenaran. Ketiga, Karya Roh Kudus. Pribadi yang sama berperan juga dalam menginspirasikan dan menyingkapkan rahasia firman. Dengan kata lain, bahwa Roh Kudus turut menopang secara aktif pelayanan Yesus Kristus dalam karya keselamatan umat manusia yang berdosa.